2011
DOI: 10.2147/ijn.s25297
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(ethylene glycol)/polylactide hybrid fibrous scaffolds for bone tissue engineering

Abstract: Polylactide (PLA) electrospun fibers have been reported as a scaffold for bone tissue engineering application, however, the great hydrophobicity limits its broad application. In this study, the hybrid amphiphilic poly(ethylene glycol) (PEG)/hydrophobic PLA fibrous scaffolds exhibited improved morphology with regular and continuous fibers compared to corresponding blank PLA fiber mats. The prepared PEG/PLA fibrous scaffolds favored mesenchymal stem cell (MSC) attachment and proliferation by providing an interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Considering that hydrophilic matrices/scaffolds may increase cell viability, the positive cell response obtained here corroborates with previous studies [36–40]. Interestingly, the present findings also agree with a previous study, which indicated that cell proliferation increased over time [51]. Previous studies reported on the enhanced mineralized matrix nodule formation in the presence of high Ca ion concentrations in dental pulp stem cells [52] and osteoblasts [53].…”
Section: Discussionsupporting
confidence: 93%
“…Considering that hydrophilic matrices/scaffolds may increase cell viability, the positive cell response obtained here corroborates with previous studies [36–40]. Interestingly, the present findings also agree with a previous study, which indicated that cell proliferation increased over time [51]. Previous studies reported on the enhanced mineralized matrix nodule formation in the presence of high Ca ion concentrations in dental pulp stem cells [52] and osteoblasts [53].…”
Section: Discussionsupporting
confidence: 93%
“…Some osteogenic markers (e.g., ALP, RUNX2, OSX and COL-I) are secreted during the early stage of osteo/odontoblastic differentiation, whereas OCN is involved in the late-stage differentiation process30313233. ALP is expressed and secreted from a proliferation phase to the deposition of mature extracellular matrix including calcium phosphate during the cell differentiation34.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 and OSX are expressed in osteogenic mesenchyme in all stages of craniofacial bone development, and RUNX2 can modulate bone and tooth development directly or through a RUNX2 signaling pathway related to OSX 32. COL-I comprises almost 90% of organic material during the formation of inorganic bone matrix to support the structure of osteogenesis333536. OCN is a small c-carboxyglutamate protein, which is synthesized only by mature cementoblasts, osteoblasts and odontoblasts, and its function is controlled by RUNX2 in the later-stage of mineralized tissues353637.…”
Section: Discussionmentioning
confidence: 99%
“…They observed no test material-related effects in mortality, inflammation, hematology, serum biochemistry parameters and organ weight in the operated animals at 8, 12, and 24 weeks after implantation [33]. Other scientists have analyzed the biocompatibility of PLA to cells and consistently report good adhesion and no acute cytotoxic effects on fibroblasts [49], MSCs [50], osteoblasts [51] or endothelial cells [52].…”
Section: Discussionmentioning
confidence: 99%